Economic burden of elderly patients with acute myeloid leukemia treated in routine clinical care in the United States. (August 2018) - Bell, Jill A.; Galaznik, Aaron; Farrelly, Eileen; Blazer, Marlo; Murty, Sharanya; Ogbonnaya, Augustina; Eaddy, Michael; Fram, Robert J.; Faller, Douglas V.; Kota, Vamsi
Graphical abstract: Highlights: Healthcare utilization in elderly acute myeloid leukemia patients is substantial. 92% of our population had ≥1 hospital admission over the course of follow-up. Treated elderly acute myeloid leukemia patients incurred significant cost. The mean cost was 25, 243 per patient per month over follow-up. Costs were higher within the first 2 months and in Year 1 after diagnosis. Abstract: This retrospective claims database study examined healthcare utilization (HCU) and costs associated with acute myeloid leukemia (AML) in 237 elderly patients who received chemotherapy or a stem cell transplant (SCT) following AML diagnosis. Patients with secondary AML were excluded. Over the entire follow-up period, 92.0% of patients had ≥1 inpatient admission; 85.7% had ≥1 AML-related admission, and 42.6% had ≥1 non-AML-related admission. During inpatient admissions, 39.2% of patients had ≥1 intensive care unit (ICU) admission, with 20.7% having ≥1 AML-related ICU admission, and 27.8% having ≥1 non-AML-related ICU admission. Total mean per-patient per-month (PPPM) costs over the follow-up period were 25, 243 (SD: 21, 909), with costs from Year 1 (27, 756 [SD: 22, 121]) more than double those in Year 2 (12, 953 [SD: 26, 334]) following AML diagnosis. The majority of total costs were medical (24, 512 PPPM [SD: 21, 704]), which included inpatient admissions (6548 PPPM [SD: 10, 777]), other outpatient visits (5021 PPPM [SD: 7997]), supportive care (3640 PPPM [SD: 5589], and chemotherapy administration (2029 PPPM [SD: 2345]). Healthcare costs of treated elderly AML patients are substantial, particularly in the first year following diagnosis. Further research is needed to understand factors contributing to high costs in various settings of care for elderly AML patients.